2021
DOI: 10.1080/0886022x.2021.1977320
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in IgA nephropathy

Abstract: IgA nephropathy (IgAN) is the most common primary glomerulonephritis worldwide. It is considered that the pathogenesis of IgAN involves the 'multiple hit theory' and the immune-inflammatory mechanism; however, these theories have certain limitations. The gold standard for diagnosing IgAN is still renal biopsy. Although renal biopsy is accurate, it is traumatic and is associated with some risks and limitations, so there is a need for non-invasive diagnostic methods. According to recent studies, microRNAs (miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 72 publications
(117 reference statements)
0
10
0
Order By: Relevance
“…miRNAs have a vital role in regulating various cellular processes, such as cell migration, proliferation and apoptosis. miRNAs are stable, ubiquitous and abundant in body fluids and cells; hence, miRNAs may be considered good biomarkers as well as drug targets (28,29). According to previous studies, miR-148b, let7b, miR-146a, miR-155, miR-21, miR-200 and miR-429 miRNAs may be involved in IgAN development (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs have a vital role in regulating various cellular processes, such as cell migration, proliferation and apoptosis. miRNAs are stable, ubiquitous and abundant in body fluids and cells; hence, miRNAs may be considered good biomarkers as well as drug targets (28,29). According to previous studies, miR-148b, let7b, miR-146a, miR-155, miR-21, miR-200 and miR-429 miRNAs may be involved in IgAN development (30).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, small RNA-seq was performed for the identification of additional functional miRNAs and the results demonstrated that nearly 75% of miRNAs were present in renal tissues from both healthy individuals and patients with IgAN. Among the 25 significant DEMs, miR-21-5p (31,32) and miR-155-5p (22,28) were previously reported to be associated with IgAN. However, the other three miRNAs, miR-146a, miR-192 and miR-146b, were newly identified in patients with IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of urinary exosomal miRNAs have been examined as surrogates of disease progression in several diseases, however, this is the rst study to differentiate IgAN-speci c miRNAs in human urine exosomes [14][15][16][17]. In this study, miR-199a-3p was the leading urinary exosomal miRNA in terms of its prognostic value for clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…IgA nephropathy (IgAN) is one of the most common primary glomerulopathies worldwide [1], and is characterized by a variable clinical course ranging from a benign condition to rapid progression to renal failure. Specifically, 15–40% of patients will develop end-stage renal disease (ESRD) within 10–20 years of onset [2].…”
Section: Introductionmentioning
confidence: 99%